2005
DOI: 10.1080/00015458.2005.11679718
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Wound Edge Necrosis by Local Application of Dimethylsulfoxide

Abstract: The application of DMSO reduced skin flap necrosis and improved outcome of surgical flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…32 Its local anesthetic effects may also reduce oxidative stress by tempering cellular excitation. 30 It is possible that a number of these effects work in concert to yield the results seen in the studies mentioned above and our experience presented here. Indeed, even a single dose of DMSO, either intra- or immediately postoperatively seems to be effective in our experience, perhaps alleviating vasospasm and oxidative stress during this critical time period.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…32 Its local anesthetic effects may also reduce oxidative stress by tempering cellular excitation. 30 It is possible that a number of these effects work in concert to yield the results seen in the studies mentioned above and our experience presented here. Indeed, even a single dose of DMSO, either intra- or immediately postoperatively seems to be effective in our experience, perhaps alleviating vasospasm and oxidative stress during this critical time period.…”
Section: Discussionsupporting
confidence: 51%
“…It is known to cause histamine release by mast cells and also increase prostaglandin E1 production, both ways in which it may induce vasodilation. 23,30,31 DMSO is also a hydroxyl-inactivating compound, giving it the ability to reduce ischemia-reperfusion injury by scavenging free radical species. 32 Its local anesthetic effects may also reduce oxidative stress by tempering cellular excitation.…”
Section: Discussionmentioning
confidence: 99%
“…Hongying and colleagues10 studied 216 women who underwent radical surgery for breast cancer and recommended less use of electrocautery, injection of adrenaline (epinephrine) into the subcutaneous tissue, routine use of drains, and the application of pressure dressings to reduce skin flap complications. Other clinical studies have indicated that local application of dimethylsulphoxide11 and transcutaneous electrical nerve stimulation12 may decrease skin flap necrosis after mastectomy. In addition, increased surgeon experience has been found to be associated with fewer postoperative complications after skin‐sparing mastectomy13.…”
Section: Discussionmentioning
confidence: 99%
“…Mastectomy, either modified radical or skin-sparing, was performed in a total of 8439 breasts from 7895 patients across studies included. Preventive non-surgical adjuncts against mastectomy flap necrosis included five different interventions: (1) Transcutaneous Electrical Nerve Stimulation, 16 (2) Topical Dimethylsulfoxide ointment (DMSO), 17 (3) Oral Cilostazol, 18 (4) Topical Nitroglycerin Ointment, [19][20][21][22][23] and (5) Closed-Incision Negative Pressure Wound Therapy (NWPT). [24][25][26] Studies reviewed included six prospective randomized trials, two prospective non-randomized trials, four retrospective cohort studies.…”
Section: Study Characteristicsmentioning
confidence: 99%